Academic Senate Minutes 2022-03-03 - Academic Senate:::::::::
Agenda Approved. Minutes of 9/21/17 Approved. Chair Report. President Report. Provost Report. Vice President of Administration and Finance Report. Theater Arts and Dance Acting Concentration Revision approved for the Senate consent calendar. Animal Care and Use in Research Policy & Cost Sharing Policy approved for the Senate agenda. APARC Report. EPC Report. SAC Report. FSAC Report. Associated Students Report. Senate agenda approved. CFA Report. Statewide Senator Report.